Do NERICA rice cultivars express resistance to Striga hermonthica (Del.) Benth. and Striga asiatica (L.) Kuntze under field conditions? - Rodenburg, J.; Cissoko, M.; Kayeke, J.; Dieng, I.; Khan, Zeyaur R.; Midega, C.A.O.; Onyuka, E.A.; Scholes, J.D. (Elsevier, 2015)
The parasitic weeds Striga asiatica and Striga hermonthica cause high yield losses in rain-fed upland rice in Africa. Two resistance classes (pre- and post-attachment) and several resistant genotypes have been identified among NERICA (New Rice for Africa) cultivars under laboratory conditions (in vitro) previously. However, little is known about expression of this resistance under field conditions. Here we investigated (1) whether resistance exhibited under controlled conditions would express under representative Striga-infested field conditions, and (2) whether NERICA cultivars would achieve relatively good grain yields under Striga-infested conditions. Twenty-five rice cultivars, including all 18 upland NERICA cultivars, were screened in S. asiatica-infested (in Tanzania) and S. hermonthica-infested (in Kenya) fields during two seasons. Additionally, a selection of cultivars was tested in vitro, in mini-rhizotron systems. For the first time, resistance observed under controlled conditions was confirmed in the field for NERICA-2, -5, -10 and -17 (against S. asiatica) and NERICA-1 to -5, -10, -12, -13 and -17 (against S. hermonthica). Despite high Striga-infestation levels, yields of around 1.8 t ha-1 were obtained with NERICA-1, -9 and -10 (in the S. asiatica-infested field) and around 1.4 t ha-1 with NERICA-3, -4, -8, -12 and -13 (in the S. hermonthica-infested field). In addition, potential levels of tolerance were identified in vitro, in NERICA-1, -17 and -9 (S. asiatica) and in NERICA-1, -17 and -10 (S. hermonthica). These findings are highly relevant to rice agronomists and breeders and molecular geneticists working on Striga resistance. In addition, cultivars combining broad-spectrum resistance with good grain yields in Striga-infested fields can be recommended to rice farmers in Striga-prone areas.